The influence of clay addition in fly ash concrete mixture for nuclear shielding - Ramli R.; Idris F.M.; Saad J.M.; Yapandi M.F.K.M.; Akmal Biyamin S. (Institute of Physics Publishing, 2023)
The disposal of ashes from power plants has caused health issues and reduce the air quality of the surrounding areas. The ashes have a potential to be used in construction of concrete mixture as partial replacement for cement. This research studies the potential fly ash and clay mixture (FAC) as a nuclear shielding material in concrete mixture. The raw materials and the testing were all done in Agensi Nuklear Malaysia. All concrete mixtures had a constant water/cement ratio of 0.266. The hardened concrete mixtures were tested for compressive strength. Scanning electron microscopy (SEM), energy dispersive X-ray (EDX) and small angle neutron microscopy (SANS) are used to characterize the properties of the mixtures. The results suggested that mixture of FAC concrete with 10% of clay addition showing good potential for nuclear shielding compared to other ratios. Published under licence by IOP Publishing Ltd.